Impacts of Bilingual Teaching job Demands and Resources on Teacher self-Efficacy- A Taiwanese Example - ChuanãChung Hsieh; Anh Hoang Khau; Hui-Chieh Li (SAGE Open)
Taiwan’s government launched the Bilingual 2030 policy to create a bilingual nation by 2030. The aim is to improve global mobility by promoting English and Mandarin Chinese proficiency. This study explores how bilingual teaching job demands—work pressure, cognitive demands, and emotional demands—and job resources impact teacher self-efficacy under this policy. Quantitative data collected from 542 content teachers in lower secondary schools were analyzed using structural equation modelling (SEM). The results showed no effects on teacher self-efficacy related to work pressure and emotional demands. However, cognitive demands harmed teacher self-efficacy. Resources focusing on teacher autonomy and professional development opportunities are significantly and positively related to teacher self-efficacy. Considering the results, the Bilingual 2030 initiatives should focus on strategies to alleviate cognitive load and increase job resources to support teachers better in each school. This result also suggests that it is crucial to address teachers’ specific needs, and from there, schools may take the initiative to address those needs promptly and effectively. Implications and practical actions of the study were presented for future reference.